Raquel's Shadow: The Representation of the Holocaust in Spanish Cultural ExpressionIn collaboration with Letras Peninsulares 22.2 (2010)Cover art courtesy of Los Campos (Vanderbilt e-Journal of Luso-Hispanic Studies, 2011)
In collaboration with Letras peninsulares 22.1 (2010)Cover art courtesy ofCampos